Susan Slade [videorecording (DVD)] - Daves, Delmer, 1904-1977; Donahue, Troy, 1936-2001; Stevens, Connie, 1938-; McGuire, Dorothy, 1918-2001; Nolan, Lloyd; Hume, Doris M., 1922-1998 (Distributed by Warner Home Video, 2009)
A pregnant teen allows her mother to pass the baby off as her own. Can Susan deny her own child, even if revealing the truth means getting a second chance at love?